If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 + -11 = 4 Reorder the terms: 3 + -11 + 6x = 4 Combine like terms: 3 + -11 = -8 -8 + 6x = 4 Solving -8 + 6x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 6x = 4 + 8 Combine like terms: -8 + 8 = 0 0 + 6x = 4 + 8 6x = 4 + 8 Combine like terms: 4 + 8 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 8(4-x)=7+2x | | 4(t-2)+11-4=2t+3 | | 7/24-1/3 | | 4+14m-1=8m+75-3m | | 9x+3x=5x+10 | | -2w+7=3x-3 | | 12-58= | | 27+1x=23 | | 5x-(12-2x)=3x | | 7.3x-1.8=20.1 | | -b=72 | | -1x+28=18 | | 10x+180=(x+10)(x+4) | | 66y=132 | | -26+5x=24 | | 21=5m+6+5 | | 12x-2=150 | | 5h-7=12(h+1) | | 72+-5x=27 | | 3k+6.2= | | 9=30n | | x*-6=4 | | 850=1.33*x | | (8y-15)2/3=14 | | 7/5/3 | | 1061=1.71*x | | 2(h+10)=59 | | h(t)=-16t^2+32x+1.5 | | -16r=-75 | | 4/5x-1/10x=9/10x | | 5t-3=(t+7)+3t | | 2x^3-x^2+16x-9=0 |